Impact of HIV on HPV-related cancers in men who have sex with men: a review - Zixuan Zhang; Zixuan Zhang; Yuying Xing; Yuying Xing; Tingdan Gong; Wanlin Li; Siwei Zhang; Lanlan Wei (Frontiers in Cellular and Infection Microbiology)
Co-infection with human immunodeficiency virus (HIV) significantly increases the incidence of human papillomavirus (HPV) infection and HPV-related cancers among men who have sex with men (MSM). Conversely, HPV infection can also influence HIV acquisition rates. HIV-induced immune suppression may affect chromosomal stability, gene expression, protein function and other molecular components in MSM with HPV-related cancers. Additionally, HIV infection also alters cellular mechanisms by compromising immune responses and epithelial integrity. In this review, we reviewed the influence of HIV on specific HPV-related cancers in MSM, including oropharyngeal squamous cell carcinoma, penile cancer, and anal cancer. We integrated epidemiological data from the past five years and discussed diagnosis and treatment strategies. Overall, our review offers crucial insights into the underlying molecular and cellular mechanisms of these co-infection MSM patients. Our review aims to assist future research in developing effective treatment strategies for MSM with HIV/HPV co-infection.